Obesity and mortality rates - Whitlock, G.; Huxley, Rachel (2014)
© 2014 by Taylor & Francis Group, LLC. Adiposity levels have risen in many countries during recent decades, and these increases have had estimable effects on particular national mortality rates. The aim of this chapter is to describe the likely effects of recent adiposity levels on cause-specific mortality rates in five selected countries: two in North America (United States and Canada), two in Europe (England and Wales-which are actually two countries but considered here as one-and France), and one in Asia (Japan). The countries were selected because of their large populations (collectively about 600 million) and because of the ready availability of reliable data for them. There are about 30 other countries to which this approach could be applied equally well, although that would be beyond the scope of a single chapter. For most of the world’s 160 or so other countries, the underlying information necessary for such estimates has simply never been collected.